2011
DOI: 10.1111/j.1553-2712.2011.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Short, Subjective Measures of Numeracy and General Health Literacy in an Adult Emergency Department

Abstract: Objectives To evaluate the reliability and validity of brief subjective measures of numeracy and general health literacy in the adult emergency department setting. Methods A convenience sample of adult emergency department patients completed subjective measures of general health literacy (Short Literacy Screening questions, SLS) and numeracy (Subjective Numeracy Scale, SNS). These patients also completed two objective tests of literacy (the Short Test of Functional Health Literacy in Adults, S-TOFHLA; and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 46 publications
(37 reference statements)
8
88
1
Order By: Relevance
“…The reported percentage of adequate health literacy was consistent with that observed in settings with comparable patient populations (Matsuyama et al, 2011;McNaughton et al, 2011). Our study was not powered to compare changes in learning across different literacy levels.…”
Section: Limitationssupporting
confidence: 75%
See 2 more Smart Citations
“…The reported percentage of adequate health literacy was consistent with that observed in settings with comparable patient populations (Matsuyama et al, 2011;McNaughton et al, 2011). Our study was not powered to compare changes in learning across different literacy levels.…”
Section: Limitationssupporting
confidence: 75%
“…We compared health literacy scores determined by the S-TOFHLA and the Chew and colleagues (2004) questions and found a correlation between the two assessments, as described previously (Chew et al, 2008;McNaughton et al, 2011). We found the Chew and colleagues (2004) questions were easier and faster to administer than the S-TOFHLA and were therefore better suited for the workflow of a fast-paced clinical setting.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Some have proposed that in preference-sensitive decisions, patients need exact probabilities of harms and benefits associated with each option to appropriately weigh the pros and cons of each; 6 however, these probabilities are often not available in EM, and even when they are, both patients and physicians may be limited by the inherent challenges of effective risk communication. [10][11][12][13][14] Finally, patients who are potentially critically ill may prefer that clinicians take a more dominant role in decision-making. [15][16][17][18] Despite nationwide efforts and focus on patient-centeredness, viewpoints of frontline practicing clinicians on how practically to achieve increased patient engagement remain largely unknown.…”
mentioning
confidence: 99%
“…Therefore, research on health numeracy is found both within health literacy studies, and in numeracy-specific articles. Subjective measures of numeracy and health literacy have indicated that they are related but unique skills (C. D. McNaughton, Rothman, R., Marcovitz, D.E., Storrow, A.B., 2011). In studies that have assessed both health literacy and numeracy in relation to the same health outcomes, numeracy has been more highly correlated with outcomes than health literacy (Marden et al, 2012; R. L. Rothman et al, 2006).…”
Section: Dewalt a 2009)mentioning
confidence: 99%